Effects of perinatal exposure to BPA and its alternatives (BPS, BPF and BPAF) on hepatic lipid and glucose homeostasis in female mice adolescent offspring. (December 2018) - Meng, Zhiyuan; Wang, Dezhen; Yan, Sen; Li, Ruisheng; Yan, Jin; Teng, Miaomiao; Zhou, Zhiqiang; Zhu, Wentao
Abstract: The widespread application of bisphenols (BPs) makes them ubiquitous in the natural environment and poses many potential risks. In this study, we examined the effects of perinatal exposure to BPA and its 3 alternatives (BPS, BPF, and BPAF) on lipid and glucose homeostasis in female mice adolescent offspring. Specifically, BPA exposure promoted the expression of hepatic lipid synthesis and fatty acid accumulation genes, resulting in a significant increase in 2 free fatty acids contents. BPS exposure caused an increase in 6 free fatty acids and triglyceride contents through promoting the expression of fatty acid synthesis, triglyceride synthesis and fatty acid accumulation genes and inhibiting the expression of fatty acid β-oxidation genes. Interestingly, BPAF exposure showed completely opposite effects on hepatic lipid metabolism compared to BPS exposure. 9 free fatty acids and triglycerides contents in the liver were significantly reduced. In particular, BPF exposure caused decreases in 2 free fatty acids contents, but no significant changes were found in the genes for lipid metabolism. In addition, unlike BPA and BPF exposure, BPS and BPAF exposure also resulted in significant increases in glucose and glycogen contents in the liver by activation of Fxr-Sh p pathway and glycolysis, and inhibition of gluconeogenesis. The results showed that compared to BPA and BPF exposure, BPS and BPAF exposure significantly regulated the expression of genes related to glucose and lipid metabolism and severely interfered with hepatic lipid and glucose homeostasis. This suggested that we should thoroughly evaluate the potential health risks of BPA and its alternatives. Graphical abstract: Highlights: BPA, BPS, BPF and BPAF interfered with the lipid and glucose homeostasis in female mice adolescent offspring to varying degrees. Compared to BPA and BPF exposure, exposure to BPS and BPAF severely affects hepatic lipid and glucose metabolism. Exposure to BPS and BPAF significantly altered the free fatty acids and triglycerides contents in the liver, but their effects on lipid metabolism were diametrically opposed. Exposure of BPS and BPAF resulted in significant decrease in glucose, α-glycogen, and β-glycogen contents in the liver.